Tenofovir Alafenamide Versus Tenofovir Disoproxil Fumarate in the First Protease Inhibitor–Based Single-Tablet Regimen for Initial HIV-1 Therapy: A Randomized Phase 2 Study. (1st August 2015) - Mills, Anthony; Crofoot, Gordon; McDonald, Cheryl; Shalit, Peter; Flamm, Jason A.; Gathe, Joseph; Scribner, Anita; Shamblaw, David; Saag, Michael; Cao, Huyen; Martin, Hal; Das, Moupali; et al.
Abstract : Objectives: To evaluate the safety and efficacy of the novel tenofovir prodrug, tenofovir alafenamide (TAF), as part of the first protease inhibitor–based single-tablet regimen (STR) for initial treatment of HIV-1 infection. Methods: Antiretroviral therapy (ART)-naive adults with estimated glomerular filtration rate ≥70 mL/min were randomized 2:1 to receive the darunavir/cobicistat/emtricitabine/tenofovir alafenamide (D/C/F/TAF) STR (TAF: N = 103) or darunavir + cobicistat + emtricitabine/tenofovir disoproxil fumarate (TDF: N = 50) once daily with matched placebos for 48 weeks. Results: At week 24, viral suppression (HIV-1 RNA <50 copies/mL) rates were similar (TAF 74.8% vs. TDF 74.0%). At week 48, rates were TAF 76.7% vs. TDF 84.0%; the difference was driven by higher rate of discontinuations in TAF (6.8%) vs. TDF (2%). Among those with virologic failure, none developed resistance. Most adverse events were of mild/moderate severity. The mean change in serum creatinine from baseline at week 48 was 0.06 mg/dL (95% confidence interval: 0.04 to 0.08) for TAF vs. 0.09 mg/dL (95% confidence interval: 0.05 to 0.14) for TDF ( P = 0.053). The % change in retinol binding protein/Cr ratio was +9 (TAF) vs. +54 (TDF), P = 0.003; the % change in urine β-2 microglobulin/Cr ratio was −42.0 (TAF) vs. +2.3 (TDF), P = 0.002. The % change in hip bone mineral density (BMD) was −0.84 (TAF) vs. −3.82 (TDF), P < 0.001 and in spine BMD was −1.57 (TAF) vs. −3.62 (TDF), P = 0.003. There were no fractures in either group. Conclusions: The TAF arm had significantly improved renal and bone safety parameters: less proteinuria and less change in hip and spine BMD, consistent with results from a similarly designed study of the elvitegravir/C/F/TAF STR. This D/C/F/TAF STR offers a promising option for initial HIV treatment, with the high barrier to resistance of darunavir, and the potential for improved long-term renal and bone safety with TAF. Abstract : Supplemental Digital Content is Available in the Text.